(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The “conceived” does not enjoy a clear legal status yet. In theory, human life deserves protection in every single step of its development: before-and-after birth and near-to-death. Practically, the condition of the ‘conceived’ ought to be ‘balanced’ with other constitutional relevant individual or general interests. While the evaluation of statute no. 194/1978, notwithstanding its flaws, is overall positive, many doubts and questions arise from the amazing genetic techniques known as CRISPR-Cas9, whose developments for the future generations have still to be certified.